Identification of active component in red pomegranate (punica granatum L.) seeds ethanolic extract - Riani Setiadhi; Irna Sufiawati; Wahyu Hidayat (DiscoverSys Inc., 2019)
Objective: Pomegranate (punica granatum L.) have many benefits for health and used as traditional medicine. The pomegranate seeds are rich in antioxidants, namely flavonoids and tannins as well as alkaloid which is an antibacterial.Â The aim of this study was to identify the pure isolate/active component of red pomegranate seeds ethanolic extract.Â Material and Methods: Two-ways TLC of the purified crystals which were obtained from the hexan fraction of ethanolic extract red pomegranate seeds, were used to make sure there was only 1 active compound of red pomegranate seeds. The isolate was identified using dragendorff, Mg and HCl, NaOH, Bunchard, Liebermen, FeCL3 and HCl concentrated reagents.Results: Isolate identification test using dragendorf reagents showed positive result (an orange-coloured).Conclusion: The pure isolate/active component of red pomegranate seeds is alkaloid.